Cultura Organizacional Cooperativa: Las Campesinas de Manquehua - Cadenas, Hugo (MAD, 2002)
<!--[if gte mso 9]> Normal 0 21 false false false ES-TRAD X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->This paper is an organizational culture diagnosis of an agro-business entity named "Las Campesinas". The organizational diagnosis defines Las Campesinas like an almost cooperative organization. The paper contains an organizational culture model and an intervention proposed.